How Do Trematodes Induce Cancer? A Possible Evolutionary Adaptation of an Oncogenic Agent Transmitted by Flukes - Péter Apari; Gábor Földvári (Evolutionary Applications)
ABSTRACT There is strong epidemiological evidence that development of various cancer types is linked to infection with flukes (Platyhelminthes: Trematoda) in Africa, Asia and the Middle East. The exact nature of the mechanism by which cancer is induced by these parasites is unknown. Here, we provide a new hypothesis suggesting that flukes are not the primary cause of cancer but act as vectors of cancer‐inducing microbial pathogens. These pathogens adaptively induce tumours to attract and help flukes to feed on blood from the tumour. Pathogen take‐up by fluke vectors also takes place in the tumour; therefore, tumour formation in this case is the result of a mutualistic and adaptive relationship between the microbe and the helminth parasite. The suggested mechanism for cancer induction provided here may help us gain deeper understanding about cancer in general and its relationship with microbes and parasites. By further elaborating the unique nexus between flukes, carcinogenic microbes and cancer, in the future it will also help us to broaden our oncological perspective to reduce human death and suffering from this serious disease group.